Difficulty in Research Subject: A Case of Teacher Education Students at Laguna State Polytechnic University, Sta Cruz Campus - Muega- Geronimo, Vilma (ASEAN Journal of Education, 2023)
The study aimed to assess the level of research difficulty of the College of Teacher Education Students in Laguna State Polytechnic University at Sta Cruz Campus as a basis for developing instructional materials in research subject. A mixed method research design was employed in this study wherein descriptive research design was utilized in the quantitative part through weighted mean and standard deviation in assessing their level of research difficulty. Meanwhile, in the qualitative part, students were asked to write their experiences in doing research, their answers were tallied, analyzed, and categorized by theme. Some items in the survey questionnaire were adopted from the research of Morales et al. (2016) and some items were included from the research course syllabus. Participants were selected through purposive sampling. The findings reveal that most of the respondents have a rating of moderately low level of difficulty on almost all items on the self-assessment survey. Students’ found high levels of difficulty in searching for relevant literature on the chosen topic of research ( ̅x = 3.53, SD = 0.93), writing a literature review ( ̅x = 3.51, SD = 0.90) and statistical analysis of data ( ̅ x = 3.43, SD = 0.98). The implication for the research professor is to consider the results in this study and to develop instructional material for the research subject that fit the needs of the students.